The Impact of Anthropomorphism on Consumers’ Evaluation of Brands: Assessing The Role of Self-Brand Congruity - Diesyana Ajeng Pramesti; Catur Sugiarto (Business Management Analysis Journal (BMAJ), 2026)
The study analyses the role of anthropomorphism in brand evaluation in Indonesia's advertisement. A quasi-experimental approach was employed to compare anthropomorphic and non-anthropomorphic advertising stimuli for a mineral water product among 242 university students. Students are suitable respondents as Gen Z and millennials who commonly engaged with branded content. Their characteristics make them relevant for studying self-brand congruity and brand evaluation. The participants were divided into two groups, each containing 121 individuals. Data were collected using a questionnaire with a 5-point Likert scale and analysed using Structural Equation Modelling with Partial Least Squares. The findings reveal that non-anthropomorphic stimuli had a p-value of 0.128, exceeding the significance threshold of 0.05, indicating a non-significant effect on brand evaluation. In contrast, anthropomorphic stimuli had a p-value of 0.014, below the 0.05 threshold, demonstrating a strong and significant impact. This confirms that anthropomorphism significantly and positively enhances consumer perceptions of brand evaluation. Additionally, self-brand congruity was found to partially mediate the relationship between anthropomorphism and brand evaluation. These findings provide valuable insights into the effectiveness of anthropomorphism strategies in the Indonesian advertising context.